Prevalence of Dermatophytosis and Antifungal Activity of Ethanolic Crude Leaf Extract of Tetradenia riparia against Dermatophytes Isolated from Patients Attending Kampala International University Teaching Hospital, Uganda. (11th July 2019) - Kakande, Taufik; Batunge, Yonah; Eilu, Emmanuel; Shabohurira, Ambrose; Abimana, Justus; Akinola, Saheed Adekunle; Muhwezi, Reagan; Sunusi Adam, Abubakar; Kemuma Onkoba, Sarah; Almustapha Aliero, Adamu; Atuheire, Collins; Kato, Charles Drago; et al.
Abstract : Dermatophyte infections are a global health problem but neglected in Uganda. This work aimed at determining prevalence of dermatophytosis and antifungal activity of ethanolic crude leaf extract of Tetradenia riparia against dermatophytes isolated from patients attending Kampala International University Teaching Hospital (KIU-TH), Uganda. A total of 100 samples of skin and nail scrapings were collected and processed using standard microscopy (KOH) and cultural methods. T. riparia leaves were collected and processed with 95% ethanol using standard extraction method. The crude leaves ethanolic extract was tested against three dermatophytes: Trichophyton tonsurans, T. mentagrophyte, and Microsporum audouinii using modified agar well diffusion method. Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of the ethanolic leaves crude extract were also determined using broth tube dilution and culture, respectively. Out of 100 samples collected, 49 (49%, 95%CI: 0.3930-0.5876) were found positive for microscopy. The prevalence of dermatophytosis was significantly (p=0.001) associated with age groups of participants with higher infection among those aged 11-20 and 21-30 years with 75.0% each. Out of the 49 that were positive by microscopy, 28 (57.15%, 95% CI: 0.1987-0.3739) were positive by culture. Thirty-one (31) fungal isolates were obtained which included both dermatophyte and non-dermatophyte fungi. T. verrucosum had highest distribution 6 (19.35%) among dermatophytes species while Aspergillus spp. were found to have highest distribution 7 (22.58%) among non-dermatophyte species. The result of the antidermatophytic test showed that T. riparia ethanolic crude leaves extract had activity against tested dermatophytes at 1 g/ml. MIC and MFC of the crude extract of T. riparia against tested dermatophytes ranged from 62.5 to 250 mg/ml and 125 to 500 mg/ml, respectively. The findings of this study reported the presence of dermatophytes causing dermatophytosis among patients attending KIU-TH. The results of the current study showed that T. riparia leaves ethanolic crude extract has antidermatophytic activity against tested dermatophytes.